Orderan Fiktif Driver Ojek Online di Kota Makassar: Studi Komparasi Hukum Nasional dan Hukum Islam - Megawati, Megawati; Arsyad, Azman; Qayyum, Abdul Rahman (Universitas Islam Negeri Alauddin Makassar, 2024)
Fictitious orders in online transportation always exist and even tend to increase and develop in society along with advances in internet technology, transportation and the economy, even though acts of fraud and fictitious orders are seen from any angle very reprehensible, because they can create mutual distrust of fellow drivers and drivers. company. The main problems in this research are 1. what is the reality of the fictitious orders of online motorcycle taxi drivers in the city of Makassar? 2. What is the comparison between national law and Islamic law against fictitious orders for online motorcycle taxi drivers? This type of research is a qualitative descriptive research with a normative (syar'i) approach and a sociological approach. Data management techniques in this study are interviews, observation and documentation. The key informants from this research are drivers and customers who make fictitious orders. The results of this study are losses felt by the customer (customers) on fictitious orders made by drivers and losses are also felt by drivers if the customer (customer) makes a fictitious order so that all those involved make fictitious orders even PT.Grab companies are not the same once taught and justified the existence of fictitious orders suffered losses. The cause of fictitious orders is due to not fulfilling the order target, the perpetrator intends to take personal advantage. The implication of this research is that companies can improve security services for online motorcycle taxi applications, as well as impose sanctions on those who make fictitious orders. Because of the lack of awareness for perpetrators to carry out fictitious orders.